Pengaruh Keterlibatan Kerja Dan Stres Terhadap Kinerja Guru SMK Swasta Kecamatan Matraman Jakarta Timur - Ahmad Fathurrohman (Universitas Indraprasta PGRI Jakarta, 2018)
This research aims to show the effects of (1) job involvement, (2) stress, (3) the performance of teachers working in Private Vocational Schools (SMK) in Matraman subdistrict, East Jakarta. The method used in the research is a survey research method with a quantitative-causal approach using path analysis. The survey was conducted from April to June 2018 by taking randomly-selected samples consisting of 150 teachers in a subdistrict. The findings in this research show: First, there is a direct effect of job involvement on performance. Second, there is a direct negative effect of stress on performance. Third, there is a negative direct effect of job involvement on stress.